Urban space and the proliferation of illegal and substandard Crèche facilities in Nigeria (2016)
There are growing concerns on the proliferation of illegal schools across the world but with less attention given to pre-school facilities which are often not categorised as schools. With abundant evidences in Nigeria, that most of these preschools metamorphose into schools, this study examines the proliferation of illegal and substandard crèche facilities in selected suburbs in Lagos State, Nigeria. Drawing on qualitative data collected from fifteen (15) proprietors and operators of crèche facilities, twenty-four (24) families with children in attendant, it was discovered that crèches were conceived as an informal business, seen as an extension of the home front. Thus the need for registration and formalisation of crèche facilities was deemed not necessary. Similarly, narratives of parents’ unwillingness to pay standard crèche fees and the unreliability of nannies accounted for the status quo. Neighbourhood location, proximity, and cost were other primary correlates for the continuous patronage of illegal and substandard crèches. The study concluded that economic concerns rather than adequate and proper wellbeing of infants cum children were major factors fostering the proliferation and patronage of illegal crèches in Nigerian urban space. There is an urgent need for the state and local councils to enact laws prohibiting substandard and illegal crèches in city centres.